NILAI HEROISME DALAM ANIME ONE PIECE “ARC WANO” DARI LAYAR KE REALITAS BUDAYA - Mukhlas, Moch; Sanubarianto, Salimulloh Tegar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2024)
Eiichiro Oda’s anime “One Piece” is known not only for its epic adventure story but also for its deep heroic values. Through the journey of Monkey D. Luffy and his friends in search of the legendary treasure “One Piece,